Molecular dynamics simulation of laser-induced interconnections of silver nanowires. (17th August 2020) - Huang, Chenchen; Cheng, Yang; Yin, Hailong; Wei, Fengqi
Abstract: In this paper, the geometric deformation and atomic behavior evolution of silver nanowires subjected to laser are simulated by non-equilibrium molecular dynamics method. The simulation results show that due to the surface plasma resonance effect of the laser, significant atomic diffusion occurs in the contact area of the two silver nanowires. With the increase of the irradiation time of the laser, the atomic diffusion becomes more and more significant, and finally the two nanowires are connected. Because it is realized in plasma resonance under the action of the connection, and diffusion joint can produce stress due to atomic focus, the stress led to the nanowire outer atomic force by the inward contraction, completely different from the whole heating lead to the phenomenon of melting, diffusion, refactoring, produce similar to the form of cold welding joint, the joint can build complete face-centered cubic lattice structure, so the laser induced nanowires connect will complete nanowires of retention of the original structure and has superior properties of the nanowires interconnect technology will become the trend of The Times, It's the most important piece of the puzzle for building the next generation of nanodevices.